2004
DOI: 10.1007/s00425-004-1261-2
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of ergoline alkaloids following treatment of Ipomoea asarifolia (Convolvulaceae) with fungicides

Abstract: Ergoline alkaloids are constituents of Clavicipitaceous fungi living on Poaceae plants. Ergoline alkaloids as well as volatile oil are also present in Ipomoea asarifolia Roem. & Schult (Convolvulaceae). Treatment of this plant with two fungicides (Folicur, Pronto Plus) eliminates the ergoline alkaloids but not the volatile oil. Elimination of ergoline alkaloids occurs concomitantly with loss of fungal hyphae associated with secretory glands on the upper leaf surface of the Ipomoea plant. Our observations sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 31 publications
3
95
0
2
Order By: Relevance
“…It is in line with these observations that Ipomoea asarifolia and related plant species belonging to the family Convolvulaceae are associated with a clavicipitalean fungus and contain ergoline alkaloids (Kucht et al, 2004;Steiner et al, 2006;Ahimsa-Mueller et al, 2007). Treatments of I. asarifolia (white blooming variety) and Turbina corymbosa (syn.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…It is in line with these observations that Ipomoea asarifolia and related plant species belonging to the family Convolvulaceae are associated with a clavicipitalean fungus and contain ergoline alkaloids (Kucht et al, 2004;Steiner et al, 2006;Ahimsa-Mueller et al, 2007). Treatments of I. asarifolia (white blooming variety) and Turbina corymbosa (syn.…”
supporting
confidence: 79%
“…Because the dmaW gene was found to be part of a cluster responsible for ergoline alkaloid biosynthesis in clavicipitalean fungi (compare Haarmann et al, 2005Haarmann et al, , 2006Fleetwood et al, 2007), the genetic material on the chromosome adjacent to this gene was also analyzed. We have previously demonstrated (Kucht et al, 2004) that alkaloids and the clavicipitalean fungi can be removed from I. asarifolia and T. corymbosa by treatment of the plant with systemic azole fungicides. Shoots of these plants rooted in garden soil grew into well-developed plants within a few weeks.…”
Section: Presence Of Genes Responsible For Ergoline Alkaloid Biosynthmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that a clavicipitaceous epibiotic fungal symbiont, Periglandula, is associated with the Convolvulaceae that produce ergot alkaloids including I. asarifolia (Kucht et al 2004, Markert et al 2008, Steiner et al 2011). More recently, it was shown that I. asarifolia contains the indole--diterpenes and that the Periglandula species associated with it contains the biosynthetic genes for both the ergot alkaloids as well as the indole diterpenes (Schardl et al 2013).…”
Section: Discussionmentioning
confidence: 99%